2007
DOI: 10.1002/aqc.873
|View full text |Cite
|
Sign up to set email alerts
|

How much variation can be explained by seasonal, spatial and environmental effects in nekton assemblages of the Terminos Lagoon?

Abstract: ABSTRACT1. The coastline is very sensitive to both climatic and human influences but also provides essential goods and services upon which human welfare depends. Species inhabiting these coastal areas provide valuable resources and enhance ecosystem functioning: it is therefore essential to understand the main factors influencing species abundance patterns. The aim of this study is to estimate the amount of variation in nekton coastal assemblages explained by spatial, temporal and environmental variables.2. Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
1
3
0
2
Order By: Relevance
“…Overfishing is one of the main reasons for the decline of fish biodiversity and fishery resources in the Beibu Gulf even the South China Sea (Chen et al, 2011;Zhang et al, 2021;Su et al, 2022). Numerous studies have revealed the importance of seasonal variations in explaining the structure and distribution of coastal nektonic communities (Hoff and Ibara, 1977;Lazzari et al, 1999;Raposa et al, 2003;Pattrick and Strydom, 2008;Ramos-Miranda et al, 2008). The results of our study further support that the environmental heterogeneity caused by seasonal variation contributes to the coastal nekton community assembly and phylogenetic diversity in the Beibu Gulf.…”
Section: Phylogenetic Diversity Of Nekton Community Increased Appreci...supporting
confidence: 82%
“…Overfishing is one of the main reasons for the decline of fish biodiversity and fishery resources in the Beibu Gulf even the South China Sea (Chen et al, 2011;Zhang et al, 2021;Su et al, 2022). Numerous studies have revealed the importance of seasonal variations in explaining the structure and distribution of coastal nektonic communities (Hoff and Ibara, 1977;Lazzari et al, 1999;Raposa et al, 2003;Pattrick and Strydom, 2008;Ramos-Miranda et al, 2008). The results of our study further support that the environmental heterogeneity caused by seasonal variation contributes to the coastal nekton community assembly and phylogenetic diversity in the Beibu Gulf.…”
Section: Phylogenetic Diversity Of Nekton Community Increased Appreci...supporting
confidence: 82%
“…Se ha detectado que la abundancia de peces de la zona marina y estuarina incrementa durante la temporada de lluvias . En cambio, la ictiofauna en la laguna de Términos muestra cambios en la abundancia y en la riqueza de manera espacial, como resultado del efecto de la descarga de ríos y la disminución de la salinidad (Ramos-Miranda et al, 2008;Sosa-López et al, 2007). Los sistemas fluvio-lagunares estuarinos Palizada y Pom-Atasta muestran variaciones temporales en la salinidad, temperatura y oxígeno disuelto, las cuales pueden verse influenciadas por la dinámica de la laguna de Términos https://doi.…”
Section: Introductionunclassified
“…In tropical and subtropical ecosystems, fish biodiversity includes widely variable forms. However, most studies on this subject have been performed based on a single gear type (Miranda et al, 2008;Rocha et al, 2010;Soeth et al, 2015;Work et al, 2017), even though different gears perform better for specific components. The use of a single gear often underestimates the species richness and the morphofunctional diversity of the system, thereby contributing to an inaccurate assessment of its health (Diekmann et al, 2005;Garcia et al, 2012).…”
Section: Introductionmentioning
confidence: 99%